2016
DOI: 10.1007/s00726-016-2359-0
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte behaviour and tissue transglutaminase expression during experimental autoimmune encephalomyelitis in transgenic CX3CR1gfp/gfp mice

Abstract: Leukocyte infiltration into the central nervous system (CNS) is a key pathological feature in multiple sclerosis (MS) and the MS animal model experimental autoimmune encephalomyelitis (EAE). Recently, preventing leukocyte influx into the CNS of MS patients is the main target of MS therapies and insight into cell behaviour in the circulation is needed for further elucidation of such therapies. In this study, we aimed at in vivo visualization of monocytes in a time-dependent manner during EAE. Using intravital t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In the present study we used two irreversible TG2 activity inhibitors to measure their effect on disease symptoms, severity and pathology in a mouse EAE model for multiple sclerosis. Our previous studies identified TG2 as a possible therapeutical target in a rat chronic relapsing EAE model in which TG2 inhibition reduced cellular infiltration as well as disease symptoms [ 13 , 34 ]. Moreover, EAE induced in C57BL/6 mice has previously been shown to be, at least partly, mediated by TG2 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we used two irreversible TG2 activity inhibitors to measure their effect on disease symptoms, severity and pathology in a mouse EAE model for multiple sclerosis. Our previous studies identified TG2 as a possible therapeutical target in a rat chronic relapsing EAE model in which TG2 inhibition reduced cellular infiltration as well as disease symptoms [ 13 , 34 ]. Moreover, EAE induced in C57BL/6 mice has previously been shown to be, at least partly, mediated by TG2 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“… 29 31 Previous research has highlighted the possible role for TG2 in the pathogenesis of MS 16 , 32 as well as in its animal model EAE. 15 , 17 , 33 In search for potential novel blood-derived biomarkers, this study reports on PBMC-derived TG2 mRNA levels in patients with MS, and in its clinical subtypes, in relation to markers of disease activity and progression.…”
Section: Discussionmentioning
confidence: 99%
“…In MS and EAE, monocytes/MdMs also accumulate in large numbers in the SAS following extravasation from the leptomeningeal vasculature or from the ChP and CSF-filled ventricles. Infiltration through leptomeningeal vessels follows increased intraluminal monocyte crawling and expression of the enzyme tissue transglutaminase 2 ( 261 ), known for its involvement in cell adhesion to fibronectin, a glycoprotein released by endothelial cells and pericytes ( 262 ).…”
Section: Myeloid Dwellers and Trespassers At Cns Interfaces Upon Automentioning
confidence: 99%